Adapting existing historical text into a mobile application design as an avenue for local history learning for the students of Tandag City - Gamaya, Marriel Ann M.; Sanchez, Samuelle Marionne C. (2023)
This media production study focused on developing a mobile application design that could serve as an avenue for local history learning for senior high school students living in Tandag City, Surigao del Sur. The main objective was to create an interactive and engaging platform that enables students to explore and comprehend the rich historical heritage of their city, using references from the book ?Tandag: Capital of Old Caraga? by Lucilo P. Trinidad. The study adopted the design thinking process to translate the existing print material into a digital application, incorporating visual communication principles and gamification elements to enhance user engagement and learning outcomes. The study employed the elements of visual communication as outlined by Dave Wood in his work on user interfaces. Color schemes, images, iconography, and metaphors were strategically utilized to enhance the visual appeal, usability, and comprehension of historical content. Gamification elements, such as leaderboards, quests, and social interaction, were incorporated to foster motivation, engagement, and collaborative learning among the students. The findings of this study contribute to the field of education and digital learning by creating a design framework and providing practical insights for the development of mobile applications focused on local history learning. The mobile application prototype called Kaagi serves as a valuable tool to strengthen and preserve the historical and cultural heritage of Tandag City through interactive learning, fostering a sense of pride, identity, and appreciation among the senior high school students of the town.
Thesis (BA Communication and Media Arts) -- University of the Philippines Mindanao, 2023